ASSOCIATION OF HEREDITARY DYSFIBRINOGENEMIA WITH PROTEIN C DEFICIENCY IN TWO PATIENTS WITH THROMBOTIC TENDENCY - Gandrille, S; Priollet, P; Capron, L; Roncato, M; Fiessinger, J N; Aiach, M (Thrombosis and Haemostasis, 1987)
An abnormal fibrinogen was found to be associated with protein C deficiency in two unrelated patients. Both were symptomatic, one having severe complicated atherosclerosis, the other recurrent venous thrombosis. In both cases, the two abnormalities coexisted in several members of the family. The two abnormal fibrinogens (Poitiers and Argenteuil) were purified from the patients' plasma and compared to fibrinogens purified from several normal subjects. Polymerisation was abnormal in both cases in presence of reptilase and thrombin.The kinetic of proteolysis by plasmin was studied during 24 hours using SDS-polyacrylamide gel electrophoresis. In the first case, the appearance of fibrinogen degradation products (FDPs) was slightly delayed. The most sliking abnormalities were observed with fibrinogen Argenteuil which still contains "early" FDPs (X and Y) at 24 h while the normal fibrinogens were all completely degraded.The stimulating effect of fibrin on plasminogen activation by tPA was studied after insolubilization of the purified fibrinogen according to the SOFIA technique described by Angles-Cano (Anal. Biochem. 1985, 153, 201). Only fibrinogen Argenteuil was found to have a decreased catalytic effect on plasmin formation.Thrombin binding by fibrin clots, studied according to Ha-verkate (Thromb. Haemostas. 1986, 55, 131) was found decreased in fibrinogen Poitiers and normal in fibrinogen Argenteuil.Conclusion: In these two cases of hereditary dysfibrinoge-nemia least one of the natural antithrombotic function elicited by fibrinogen-fibrin transformation was found to be strongly abnormal . Both fibrinogens presented abnormal lysis by plasmin, particularly fibrinogen Argenteuil in which Tibnn degradation was also reduced. This functional abnormality have already been described in patients with thrombotic tendency. It is however difficult to conclude, as in both families the dysfibrinogenemia was associated with protein C deficiency.